Pancreatitis-induced prediabetes and hepatic lipidosis in a mixed breed cat - Siti Faridha Amalia Ihsanu Nadya; Chairunnisa, Arvia; Windria, Sarasati; Eka Rifki, Prananda (ARSHI Veterinary Letters, 2024)
Pancreatitis can lead to decreased insulin production and elevated blood glucose levels. Reduced insulin levels can cause excessive lipolysis, leading to hepatic lipidosis. This report aimed to illustrate how pancreatitis can result in prediabetes and hepatic lipidosis, providing insight into selecting appropriate and causal therapies. This case report discusses a 5-year-old male mixed-breed cat weighing 3.9 kg presented with anorexia and hypersalivation. Despite a routine physical examination, blood tests revealed decreased creatinine and Ca2+ levels and elevated blood glucose, SGPT, cholesterol, and amylase levels. These findings suggested a diagnosis of pancreatitis accompanied by prediabetes and hepatic lipidosis. The treatment administered included intravenous Ringer’s Lactate, subcutaneous Ornipural® injection, oral cephalexin (Rilexine®) and Samylin®, and dietary management with specialized renal wet food.